Corporate Sustainability Accounting and Financial Performance of Listed Construction Companies in Nigeria - Tonye Young-Arney; Onowu, Joseph Uche (International Journal on Economics, Finance and Sustainable Development, 2022)
The study examined corporate sustainability accounting and financial performance of listed construction companies in Nigeria. The specific objective of the study was: among others to; examine the relationship between community’s environmental costs and earnings per share of listed construction companies in Nigeria, examine the relationship between human capital development costs and earnings per share of listed construction companies in Nigeria. examine the relationship between social community development costs and earnings per share of listed construction companies in Nigeria. Ex-post facto research design was employed. The population of the study was the six (6) listed construction companies with complete financial statements in the Nigerian Stock Exchange 2022.The instrument of the study is secondary data. The formulated research questions were analysed with descriptive statistics, while simple regression analysis was adopted to test the hypotheses. The findings of the study among others were that; there is no significant relationship between community’s environmental costs (CEC) and earnings per share (eps) of listed construction companies in Nigeria.